(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
River terraces and floodplains indicate channel-sediment dynamics and represent important landform features, which can be used to untangle the evolutionary history of climate and tectonic conditions in a certain area. With the availabil- ity of high-resolution topographic data, it has recently become feasible to apply GIS procedures for the identification of these subtle landform features. In this study, the TerEx Toolbox, a GIS extension for semiautomatic terrace extraction was applied on the LiDAR based DEM of the Sava River, west of Zagreb in Croatia. The aim of this research was to compare results obtained by TerEx to the existing geological map from the 1970s, which shows sediments of the recent flow (rou- tinely flooded area) and two abandoned Holocene river terraces in the study area. The TerEx output was validated using hillshaded DEM, a historical map of the study area, orthophoto imagery, topographic cross sections and field investiga- tions. TerEx has successfully extracted Holocene terraces and risers shown on the geological map but in some parts of the study area, their position and extent was different. The presented study shows that results obtained by TerEx, in particu- lar if used in combination with other data sources, can effectively focus fieldwork and contribute to new unbiased inter- pretation of terrain morphology.